The effects of macroeconomic indicators to Malaysian government bond yield from year 2008-2018 - Nor Nadia Atiqah, Ahmad (2021)
Purpose – The purpose of this paper is to demonstrate the effect of macroeconomic indicators namely towards the Malaysian government bond yield for a period from year 2008 until 2018. Design/Methodology/Approach – This study used static panel regression which includes pooled Ordinary Least Square (OLS) model to analyse the effect of five macroeconomic indicators namely, Foreign Direct Investment (FDI), Consumer Price Index (CPI), Government Debt (GD), Short-Term Interest Rate (STIR) and Exchange Rate (FX) on Malaysian government bond yield. Findings – The finding supports the expected hypotheses that FX and GD are significant to explain Malaysia government bond yield. However, FDI, CPI and STIR have weak and no influences on government bond yield respectively which contradicted from the other researchers’ finding. Therefore, to ensure there are no theoretical problem occur, the diagnostic checking then is carried out to latent the unearth econometrics defect. Originality/value – This is an original study based on compilation of data from secondary sources. The findings will provide invaluable information on the determining the factors that may contribute to the movement in bond yield to financial regulatory policymakers, participation in bond market, institutional players and researchers. Further future study on bond market should incorporate the Islamic and conventional types of bonds as well as government and corporate bonds to understand the behaviour of different types of bond. In addition, future research should also consider other factors that could affect bond yield spread such as money supply. Extending this study to other market and incorporate other macroeconomic variablesis worth pursuing for additional literature.